The Impacts of Zoning System Policies of New Students’ Admission on the Education Quality Equalization - Safitri, Dhamar Widya; Istiyono, Edi (LPPM Undiksha, 2022)
New Students’ Admission (here termed as PPDB) aims to support the Indonesia country in the education quality equalization. For this, there is a need for research to observe the impacts of PPDB on the education quality. This research aims to describe the procedure in the preparedness, implementation, and impacts of zoning system policies of PPDB on the education quality equalization in middle schools in Bantul Regency, Yogyakarta. This quantitative research was conducted using the discrepancy evaluation model developed by Malcolm M. Provus. The respondents involved included the principals, PPDB committee, students and students’ guardians representing five zones as determined in Bantul Regency. The technique of collecting data was conducted using the questionnaires, interview and documentation. The content validity was carried out using Cronbach’s Coefficient Alpha. Meanwhile, the data analysis used was the descriptive-quantitative and canonical test. This research on the implementation of PPDB using zoning system in Bantul Regency showed the following results: the zoning system policies in PPDB had no a significant impact on the quality equalization of education at middle schools in Bantul Regency. Overall, the completeness of the supporting equipment for the learning process at state middle schools in Bantul Regency has been available and and running well. The PPDB committee stated that there has been no change in education management both before and during the zoning system policy in PPDB. Thus, there is no change in the education quality.